Basic principles of colloid science - Everett, D. H. 1916-2002 (Royal Society of Chemistry paperbacks., 1988)
This book provides an introduction to colloid science, based on the application of the principles of physical chemistry. Early chapters assume only an elementary knowledge of physical chemistry and provide the basis for more thorough discussion in later chapters covering specific aspects of colloid science. The widespread occurrence of colloids is stressed and the more important industrial applications of colloid technology are outlined. The final chapter deals with the future of colloid science and indicates the directions in which further developments are likely to take place. The book is ideal for undergraduate courses and, supplemented by further reading, for postgraduates too. It will also be useful to industrial research workers who wish to become familiar with the basic ideas and their many important applications to industry.